Will Tirzepatide become a game-changer in the pharmacological treatment of obesity? - literature review - Doryń, Aleksandra; Woźniak, Kinga; Jung, Magdalena; Jung, Maximilian; Hedesz, Patryk; Warzycka, Klaudia; Gardian-Baj, Monika; Szczerbiak, Alicja; Ulicka, Wiktoria; Kuśmierczyk, Katarzyna; et al. (Journal of Education, Health and Sport, 2024)
Introduction and objective: Obesity has become an important public health issue in Poland. Furthermore, it is one of the most common preventable causes of diseases and mortality. Pharmacological methods of treating obesity have been developing significantly in recent years.Tirzepatide is a new dual incretin receptor agonist that activates both GIP (glucose-dependent insulinotropic polypeptide) and GLP-1 (glucagon-like peptide-1) receptors. The aim of this review is to assess the effectiveness of this medication in reducing body weight. Current state of knowledge: According to data from the Central Statistical Office (GUS) in Poland, 65% of men and 49% of women are struggling with the issue of excessive body weight [1]. Obesity in Polish society is steadily increasing in every age group. However, it affects most significantly children aged 7-13 years and adolescents. In 2022, the novel dual GLP and GIP-1 agonist has been registered for the treatment of type 2 diabetes which is not satisfactorily controlled. It can be also used together with diet and physical activity in patients diagnosed with obesity (BMI of 30 kg/m2 or more) or who are overweight (BMI 27-30 kg/m2) and have weight-related health problems such as hypertension, metabolic syndrome, dislipidaemia and diabetes mellitus [2]. Summary: The increasing prevalence of obesity leads to a dynamic search for the most effective pharmacological methods of treating obesity. The combined activation of GLP-1 and GIP receptors by Tirzepatide has been shown to have additional benefits beyond satisfying glucose control. The biological mechanism of action of this medication additionally causes decreased food intake, slowed gastric emptying and enhanced insulin secretion, all of which can contribute to weight reduction.